Establishing Patient-Derived Cancer Cell Cultures and Xenografts in Biliary Tract Cancer - Kang, Jihoon; Lee, Ji-Young; Lee, Sunmin; Kim, Danbee; Lim, Jinyeong; Jun, Ha Ra; Jeon, Seyeon; Kim, Young-Ae; Park, Hye Seon; Kim, Kyu-pyo; Chun, Sung-Min; Lee, Hee Jin; et al. (Cancer research and treatment, 2023)
PurposeBiliary tract cancers (BTCs) are rare and show a dismal prognosis with limited treatment options. To improve our understanding of these heterogeneous tumors and develop effective therapeutic agents, suitable preclinical models reflecting diverse tumor characteristics are needed. We established and characterized new patient-derived cancer cell cultures and patient-derived xenograft (PDX) models using malignant ascites from five patients with BTC.Materials and MethodsFive patient-derived cancer cell cultures and three PDX models derived from malignant ascites of five patients with BTC, AMCBTC-01, -02, -03, -04, and -05, were established. To characterize the models histogenetically and confirm whether characteristics of the primary tumor were maintained, targeted sequencing and histopathological comparison between primary tissue and xenograft tumors were performed.ResultsFrom malignant ascites of five BTC patients, five patient-derived cancer cell cultures (100% success rate), and three PDXs (60% success rate) were established. The morphological characteristics of three primary xenograft tumors were compared with those of matched primary tumors, and they displayed a similar morphology. The mutated genes in samples (models, primary tumor tissue, or both) from more than one patient were TP53 (n=2), KRAS (n=2), and STK11 (n=2). Overall, the pattern of commonly mutated genes in BTC cell cultures was different from that in commercially available BTC cell lines.ConclusionWe successfully established the patient-derived cancer cell cultures and xenograft models derived from malignant ascites in BTC patients. These models accompanied by different genetic characteristics from commercially available models will help better understand BTC biology.